A Case of Farmer Adaptation and Adoption of Contour Hedgerows for Soil Conservation - Fujisaka, Sam (Cambridge University Press, 1993)
After farmer-to-farmer training, farmers at an upland research site in the Philippines adapted and adopted contour hedgerows over a period of four years. They developed hedgerow establishment methods that required less labour, eliminated grasses that were too competitive with crops, stopped planting trees that were initially intended to produce green manures, and planted species that might provide direct cash returns. The different systems they used controlled soil erosion equally and effectively, although grazing of hedgerows by neighbours’ cattle was a problem. The farmers who learned about the technology but who did not establish contour hedgerows on their farms were those who had a higher proportion of flat land and/or off -farm or non-farm income opportunities.